The Role of Anionic Protein Residues on the Salt Dependence of the Binding of Aminoacyl-tRNA Synthetases to tRNA: A Poisson-Boltzmann Analysis (Communications in Computational Physics, 2008)
Long-range electrostatic interactions in proteins/peptides associating to nucleic acids are reflected in the salt-dependence of the binding process. According to theoligocationic binding model, which is based on counterion condensation theory, onlythe cationic residues of peptides/proteins near the binding interface are assumed toaffect the salt dependence in the association of peptides and proteins to nucleic acids.This model has been used to interpret and predict the binding of oligocationic chains–such as oligoarginines/lysines–to nucleic acids, and does an excellent job in thesekinds of systems. This simple relationship, which is used to compare or count the number of ionic interactions in protein-nucleic acid complexes, does not hold when acidicresidues, i.e. glutamate and aspartate, are incorporated in the protein matrix. Here,we report a combined molecular mechanics (by means of energy-minimization of thestructure under the influence of an empirical energy function) and Poisson-Boltzmann(PB) study on the salt-dependence in binding to tRNA of two important enzymes thatare involved in the seminal step of peptide formation in the ribosome: Glutaminesynthetase (GluRS) and Glutaminyl synthetase (GlnRS) bound to their cognate tRNA.These two proteins are anionic and contain a significant number of acidic residuesdistributed over the entire protein. Some of these residues are located in the bindinginterface to tRNA. We computed the salt-dependence in association, SKpred, of theseenzyme-tRNA complexes using both the linear and nonlinear solution to the Poisson-Boltzmann Equation (PBE). Our findings demonstrate that the SKpred obtained withthe nonlinear PBE is in good agreement with the experimental SKobs, while use of thelinear PBE resulted in the SKpred being anomalous. We conclude that electrostatic interactions between the binding partners in these systems are less favorable by means ofcharge-charge repulsion between negatively charged protein residues and phosphate oxygens in the tRNA backbone but also play a significant role in the association process of proteins to tRNA. Some unfavorable electrostatic interactions are probably compensated by hydrogen-bonds between the carboxylate group of the side chain in theinterfacial acidic protein residues and the tRNA backbone. We propose that the low experimentally observed SKobs values for both GlnRS- and GluRS-tRNA depend on thedistribution and number of anionic residues that exist in these tRNA synthetases. Ourcomputed electrostatic binding free energies were large and unfavorable due to theCoulombic and de-solvation contribution for the GlnRS-tRNA and GluRS-tRNA complexes, respectively. Thus, low SKobs values may not reflect small contributions fromthe electrostatic contribution in complex-formation, as is often suggested in the literature. When charges are "turned off" in a computer-experiment, our results indicatedthat "turning off" acidic residues far from a phosphate group significantly influencesSKpred. If cationic residues are "turned off", less impact on SKpred is observed withrespect to the distance to the nearest phosphate-group.